The state of our children's homes: a descriptive study of conditions and resources within childrens homes in the greater Johannesburg area with special reference to the impact of the HIV/AIDS epidemic on these facilities and the training/expertise of caregivers working in these homes - Meiring, Michelle Adrienne (My University, 2008)
INTRODUCTION The HIV epidemic in South Africa has increased not only the number of ill children but also the number of orphans. Although the establishment of orphanages is not sustainable, the number of residential care facilities continues to increase. Many persons working in South African children s homes can testify to the impact HIV has had on this sector, but no studies have actually measured it. AIMS The primary aim of this research was to determine the impact of HIV on the Johannesburg children s homes. The secondary aims were to make recommendations informed by this research to assist children s homes to mitigate the impact and to inform the activities of the Children s Homes Outreach Medical Programme (CHOMP). METHODS A rapid appraisal of all children s homes in the greater Johannesburg was done by means of a telephonic survey. This was followed by an in depth analysis of 24 children s homes through the use of questionnaires, data collection forms, a pop quiz for residential child care workers and the inspection of facilities. RESULTS A total of 115 residential care facilities with a population (excluding the special needs homes) of 5 934 were identified. In a sample of 24 homes, 31,7% of the children were HIV affected and 20% HIV infected. The morbidity rate in the homes was 10%, and 99% of this morbidity was attributable to HIV/AIDS. Over a 6 month period 57 children died in the children s homes, 93% from HIV related conditions.
Keywords: children's homes; johannesburg; HIV/AIDS; impact; training/expertise of caregivers; conditions; resources